Diseño de una Colección de Indumentaria para la comunidad Drag Queen de la Fundación Visión y Diversidad de Tungurahua - Alison Micaela, Jiménez Moyano (2025)
This project proposes the design of a collection of clothing for the Drag Queen community of Tungurahua, this initiative seeks to address and understand the specific needs of this community, who for a long time have faced limitations in access to clothing or costumes appropriate to their art and character, which is why they have been forced to resort to the importation of clothing, accessories and footwear, which implies that the costs are very high and even the waiting time is very long or can be scammed by online pages. The proposal is based on an innovative approach that integrates extravagant designs, bright, ethnic textiles, vibrant color palette and ergonomic considerations, also the implementation of rhinestones, feathers, volume in garments and structures that make the costume more striking and empower the Drag Queen artist. These elements not only help to highlight the artistic expression, but also have a symbolic message that helps to better represent their character, identity and creativity. In Ecuador and around the world Drag Art is considered as a form of artistic expression thattransform s masculinity and creates very extravagant female characters taking it to exaggeration to break gender norms and challenge the traditional with the implementation of wigs, long nails, big eyelashes, skirts, heels and makeup transformist. The importance of this art is what they want to transmit as their Ecuadorian roots and their way of seeing the world and problems around them. The research used for the development of this project was called the nine areas of design, complemented with semi-structured interviews, observation sheets and bibliographic research. These approaches allowed the identification of preferences, needs and styles of Drag Queen costumes. Likewise, cultural elements of the Ecuadorian festivities were incorporated in the designs, achieving an authentic, extravagant and elegant collection. Finally, we made an extravagant costume that combines elegance with culture and gives a real drag queen to enhance it and transmit innovation by offering unique and distinctive garments.